Network Device Firmware Process Automation : need, challenges and Solutions - Mohit Bajpai (North American Journal of Engineering Research, 2021)
Firmware is like the brain of any network device. it guides a network device how to operate, therefore upgrading firmware as needed is critical for maintaining the security, performance, and functionality of network devices. This paper provides a detail of the firmware upgrade process, including the preparing for the upgrade, execution, and post-upgrade verification. Importance is given to understanding the need for upgrades, the benefits they offer, and the challenges associated with the upgrade process. Following the process ensures that network bias remain secure and effective, supporting the ongoing demands of modern network structure.